1933
DOI: 10.4039/ent65145-7
|View full text |Cite
|
Sign up to set email alerts
|

The Larval Development of Three Barkbeetles

Abstract: The application of Dyar's Law to lepidopterous larvae has been discussed by numerous investigators, who have shown that in many species the head-widths follow a regular geometrical progression in successive instars. Taylor reviews Dyar's Law thoroughly and tests it out on the sawfly, Phyllotoma nemorata (Fallen). The same author examines Dyar's measurements on 46 species of sawfly larvae and concludes that Dyar's Law holds as well for the sawfly larvae as for the 28 species of lepidopterous larvae on which the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0

Year Published

1939
1939
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 0 publications
5
22
0
Order By: Relevance
“…Our data, as expected, revealed a linear progression; Trimble's data were nonlinear (Table 3) and did not follow the regular geometric progression described by Dyar (1890). Prebble (1933) and Reid (1962) showed that Dyar's rule was applicable to the bark beetles Dendroctonus simplex LeConte and D. ponderosae, respectively. The rate of change reported in these two studies was approximately 0.75, similar to our findings for P. mexicanus (Table 3).…”
Section: Instarssupporting
confidence: 74%
“…Our data, as expected, revealed a linear progression; Trimble's data were nonlinear (Table 3) and did not follow the regular geometric progression described by Dyar (1890). Prebble (1933) and Reid (1962) showed that Dyar's rule was applicable to the bark beetles Dendroctonus simplex LeConte and D. ponderosae, respectively. The rate of change reported in these two studies was approximately 0.75, similar to our findings for P. mexicanus (Table 3).…”
Section: Instarssupporting
confidence: 74%
“…with those made byPrebble (1933) a t Fredericton, N.B. with those made byPrebble (1933) a t Fredericton, N.B.…”
mentioning
confidence: 75%
“…Our results are consistent with DyarÕs rule, which states that head capsule increases geometrically, that is, Ϸ1.4 (Dyar 1890). Since 1890, the application of DyarÕs rule to Lepidoptera and Coleoptera has been discussed (Prebble 1933, Kaston and Riggs 1937, Kishi 1971, Mizell and Nebeker 1979. Gaines and Campbell (1935) qualiÞed the use of frequency distributions, saying these "will give clear results only when the insects measured are fairly homogenous in rate of development and number of instars."…”
Section: Discussionmentioning
confidence: 99%